Social Work in Psychosocial Crises: Analysis of a Voluntary Psychosocial Counseling Program to Close a Supply Gap in Psychosocial Therapy - Andreas, Franke; Stefanie, Neumann; Danuta, Franke; Robert, Northoff (Journal of Preventive Medicine And Care, 2017)
Background: People suffering from acute psychosocial crises often require immediate help. To supplement existing institutions and services, a counseling program (“Hel.p”) was founded; this study evaluates that program following a two-year trial period. Methods: The program offered anonymous, free-of-charge appointments to the public conducted by consultants holding, at minimum, a bachelor’s degree in social work. Supervised by a judge and a psychologist, client-centered counseling sessions were conducted each week. Results: Thirty-five counselors counseled 70 people. The clients were 37.6 +/- 18.4 years old and mostly female (67.1%). The counseling topics included health and diseases (16.1%) and general family problems (11.3%). The majority of the sessions (63.5%) took place during acute psychosocial crises. Conclusions: “Hel.p” functions as a supplement to established outreach clinics for people with acute psychosocial crises. It bridges the gap between individuals’ acute psychosocial problems and the delayed psychiatric/psychotherapeutic treatment caused by resource restrictions in the health care system.
Keywords: psychosocial; social work; crises; outreach clinic; psychotherapy